ETIOLOGY, CLINICAL MANIFESTATIONS, TREATMENT AND PREVENTION OF TICK-BORNE ENCEPHALITIS - A. G. Gaivoronskaya; M. G. Galitskaya; L. S. Namazova-Baranova; А. Г. Гайворонская; М. Г. Галицкая; Л. С. Намазова-Баранова (Pediatric pharmacology, 2013)
At present, tick-borne encephalitis is registered in Siberia, Far East, Urals, Belarus and central regions of Russia. The viral infection has also been recently revealed among the population of the previously problem free regions: Penza, Yaroslavl, Magadan, Kamchatka, Moscow and Ivanovo. The disease manifests itself in various forms: febrile, meningeal, meningoencephalitic etc. The disease prognosis is favorable in case of a meningeal or febrile form, but significantly worse in case of a meningoencephalitic form – fatal outcomes take place in 25-30% of cases. Residuals in the form of convulsive hyperkinetic syndrome may remain in some patients even if the treatment started in time. Active immunization is the primary tick-borne encephalitis prevention. В настоящее время клещевой энцефалит регистрируется в Сибири, на Дальнем Востоке, Урале, в Беларуси и центральных областях страны. В последнее время вирусная инфекция стала выявляться и среди населения ранее благополучных областей: Пензенской, Ярославской, Магаданской, Камчатской, а также Московской и Ивановской. Заболевание проявляется в различных формах: лихорадочной, менингеальной, менингоэнцефалитической и других. При менингеальной и лихорадочной формах прогноз благоприятный. При менингоэнцефалитической ― существенно хуже, летальные исходы достигают 25−30%. Даже при своевременном начале лечения у отдельных больных могут сохраняться остаточные явления в виде судорожного, гиперкинетического синдромов. Важной и основной профилактикой клещевого энцефалита служит активная иммунизация.